Corticosteroid Treatment Impact on Spinal Deformity in Duchenne Muscular Dystrophy. (29th October 2014) - Sanzarello, Ilaria; Merlini, Luciano; Traina, Francesco; Rosa, Michele Attilio; Faldini, Cesare
Abstract : Duchenne muscular dystrophy is a progressive disease with loss of ambulation at around 9-10 years of age, followed, if untreated, by development of scoliosis, respiratory insufficiency, and death in the second decade of life. This review highlights the natural history of the disease, in particular, with regard to the development of the spinal deformity and how this complication has been modified by surgical interventions and overall by corticosteroid treatment. The beneficial effect of corticosteroids may have also an impact on the clinical trial design of the new emerging causative therapies.